Thermal-structural Coupling Analysis of Friction Pair of Hydro Viscous Speed Regulating Clutch - Wang Yun; Chen Zhe; Chen Liyu; Cui Jiasen; Yang Xiaming (Jixie chuandong)
Based on the heat conduction theory,combining the thermal flux density,considering convective heat transfer in the groove on the friction pairs,a theoretical model of the friction pairs of the hydro viscous speed regulating clutch is established. According to the actual working condition of clutch,numerical analysis for the boundary friction stage of friction pair is performed,and the difference of temperature and deformation under different material combinations of friction pairs is studied. The results show that the temperature field of friction pairs is divided into elliptical blocks of different temperature gradient by the groove,and high temperature is concentrated near the outside diameter. Under the same conditions,the temperature and deformation is biggest when the dual material is 30 Cr Mn Si A. The internal and external diameters of the friction pairs occur positive and negative displacements along the z axis,and disc buckling occurs. It is found that only 30 Cr Mn Si A doesn’t undergo plastic deformation in case of the outer diameter having constraint. This is meaningful for the mechanism of hydro viscous transmission and active design of friction pairs.